Cracking the organic chemistry: unleashing precision learning with smart questions in ChatGPT - Antypenko, O. M.; Antypenko, L. M.; Антипенко, Олексій Миколайович (Одеса : Гельветика, 2024)
The path to mastering any subject becomes an exciting adventure to strategically unravel its complexities through a variety of thoughtprovoking questions. In Organic Chemistry education, the art of questioning becomes a key strategy for gaining accurate knowledge.